The Implementation of an Integrated Pull System to Improve Work Effectiveness in the Raw Material Laboratory of PT. XYZ - Aproditha Alya Chairani; Silvia Merdikawati; Ni Made Sudri (Institut Teknologi Dirgantara Adisutjipto, 2026)
PT. XYZ is a company in the cosmetics sector. In its product development process, the raw material laboratory in the R&D division experienced obstacles in the raw material trial process, which caused 15.2% of trial journals to be temporarily halted and placed on hold. This research was conducted to maintain the availability of raw materials in the laboratory and improve the smoothness of the trial process. The approach used was quality control and improvement through the concept of a pull system, lean manufacturing, and the Quality Control Circle method. Improvements made included the implementation of a pull system for raw material management, rescheduling of checking and material preparation pickets, and strengthening personnel discipline towards SOPs in all trial stages. The evaluation results showed a decrease in the number of obstacles per week from 10 obstacles to 0 obstacles in the 10th week of 2025. This research contributes to providing a model for improving laboratory efficiency through the integration of a pull system to increase speed and accuracy in the product development process.